Clinical Outcomes of 2-Drug Regimens vs 3-Drug Regimens in Antiretroviral Treatment–Experienced People Living With Human Immunodeficiency Virus. (23rd December 2020) - Greenberg, Lauren; Ryom, Lene; Neesgaard, Bastian; Wandeler, Gilles; Staub, Therese; Gisinger, Martin; Skoll, Michael; Günthard, Huldrych F; Scherrer, Alexandra; Mussini, Cristina; Smith, Colette; Johnson, Margaret; et al.
Abstract: Background: Limited data exist that compare clinical outcomes of 2-drug regimens (2DRs) and 3-drug regimens (3DRs) in people living with human immunodeficiency virus. Methods: Antiretroviral treatment–experienced individuals in the International Cohort Consortium of Infectious Diseases (RESPOND) who switched to a new 2DR or 3DR from 1 January 2012–1 October 2018 were included. The incidence of clinical events (AIDS, non-AIDS cancer, cardiovascular disease, end-stage liver and renal disease, death) was compared between regimens using Poisson regression. Results: Of 9791 individuals included, 1088 (11.1%) started 2DRs and 8703 (88.9%) started 3DRs. The most common 2DRs were dolutegravir plus lamivudine (22.8%) and raltegravir plus boosted darunavir (19.8%); the most common 3DR was dolutegravir plus 2 nucleoside reverse transcriptase inhibitors (46.9%). Individuals on 2DRs were older (median, 52.6 years [interquartile range, 46.7–59.0] vs 47.7 [39.7–54.3]), and a higher proportion had ≥1 comorbidity (81.6% vs 73.9%). There were 619 events during 27 159 person-years of follow-up (PYFU): 540 (incidence rate [IR] 22.5/1000 PYFU; 95% confidence interval [CI]: 20.7–24.5) on 3DRs and 79 (30.9/1000 PYFU; 95% CI: 24.8–38.5) on 2DRs. The most common events were death (7.5/1000 PYFU; 95% CI: 6.5–8.6) and non-AIDS cancer (5.8/1000 PYFU; 95% CI: 4.9–6.8). After adjustment for baseline demographic and clinical characteristics, there was a similar incidence of events on both regimen types (2DRs vs 3DRs IR ratio, 0.92; 95% CI: .72–1.19; P = .53). Conclusions: This is the first large, international cohort to assess clinical outcomes on 2DRs. After accounting for baseline characteristics, there was a similar incidence of events on 2DRs and 3DRs. 2DRs appear to be a viable treatment option with regard to clinical outcomes. Further research on resistance barriers and long-term durability of 2DRs is needed. Abstract : In this analysis of 9791 antiretroviral-experienced individuals in the International Cohort Consortium of Infectious Diseases (RESPOND) (1088 on 2-drug regimens, 8703 on 3-drug regimens), there was a similar short-term incidence of severe clinical events after adjusting for baseline characteristics (incidence rate ratio, 0.92; 95% confidence interval, .72–1.19; P = .53).